Differences in adoption of COVID-19 pandemic related preventive behaviour by viral load suppression status among people living with HIV during the first wave of the pandemic - Folayan Morenike Oluwatoyin; Abeldaño Zuñiga Roberto Ariel; Aly Nourhan M; Ellakany Passent; Idigbe IfeomaE; Jafer Mohammed; Lawal Folake B; Khalid Zumama; Lusher Joanne; Virtanen Jorma I; Nguyen Annie L. (Biomed Central, 2025)
Background: Adherence to antiretroviral therapy and COVID-19 preventive behaviours among people living with HIV during the pandemic has received little attention in the literature. To address this gap in knowledge, the present study assessed the associations between viral load, adherence to antiretroviral therapy and the use of COVID-19 prevention strategies during the first wave of the COVID-19 pandemic. This was a secondary analysis of data generated through an online survey recruiting participants from 152 countries. Complete data from 680 respondents living with HIV were extracted for this analysis.
Results: The findings suggest that detectable viral load was associated with lower odds of wearing facemasks (AOR: 0.44; 95% CI:0.28-0.69; p < 0.01) and washing hands as often as recommended (AOR: 0.64; 95% CI: 0.42-0.97; p = 0.03). Also, adherence to the use of antiretroviral drugs was associated with lower odds of working remotely (AOR: 0.60; 95% CI: 0.38-0.94; p = 0.02). We found a complex relationship between HIV positive status biological parameters and adherence to COVID-19 preventive measures that may be partly explained by risk-taking behaviours. Further studies are needed to understand the reasons for the study findings.